WORK ACTIVITIES AFFECTING MYOPIA PREVELENCE - Endiyono, Stylla Vonch; Saryono, Saryono (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Introduction: One of the eye diseases experienced by children, adults, and the elderly is Myopia. Myopia is a refractive error in the eye where the resulting image point falls in front of the retina. Time spent on near vision work and lack of outdoor activities are environmental factors of great concern .The purpose of this scoping review is to find out how work activities affect the prevalence of myopia. The method in this study uses the literature study method. The data was carried out by searching the Science Direct database, the Oxford Journal and Google Scholar. The result of this scoping review is that myopia is caused by using computers at a young age and sitting too much to read indoors which causes myopia and efforts to prevent myopia are by limiting the use of computer screens and doing outdoor activities.